Sistem Diagnosis Kerusakan Mesin Fotocopy Canon iR 5000 - Dwi Yuli Prasetyo (Program Studi Teknik Industri, 2019)
A photocopier is one of the devices needed in the printing business. The photocopier used by small companies in Indonesia is the Canon photocopier, Canon's trademark is well-known and quality in the safe. Photocopier technology is increasingly growing with the times. Once invited by Canon photocopiers, there are many variants of Canon photocopiers that can be marketed in Indonesia from the latest series to the old series, the writer takes one sample, using a Canon iR5000 copy machine, because this photocopier is widely used by small devices, so it is very it's easy to find research samples. During this time when there is damage or error in the Canon iR5000 copy machine the user will ask a technician who is an expert in the copy machine, to help repair the damage to the copy machine, so the user requires additional costs in maintenance. Therefore, an expert system will be designed to diagnose damage to the Canon iR5000 photocopier, with this expert system will help users of the Canon iR5000 photocopier in dealing with machine software error machine errors, so that users are comfortable and calm in using the copier, anything will increase use value for photocopiers, so it can be used to increase sales turnover for small and medium businesses.